Pengembangan Buku Ajar Berbasis Praktek Pada Mata Kuliah Tenis Lapangan di IKIP Budi Utomo - Irwansyah, Irwansyah; Junaidi, Ahmad (Journal Sport Area, 2019)
This research intends to develop textbooks based on the practice of theoretical and practice subjects of field tennis for students of physical education of health and recreation major. The method that used in this research is the research and development method of brog and gall. This development results in a product in the form of a practice-based textbook on theoretical and practice courses of field tennis. The results of the analysis of this research data are at 84.41% which means that this textbook is proper to be used as teaching material for theory and practice course of field tennis for health and recreation physical education students IKIP Budi Utomo Malang.